Examining the coach-athlete relationship for facilitators and barriers to healthy sport participation for cyclically menstruating athletes: A systematic review - Gopalan, S.; Liu, S.; Mann, C.; Buckler, E. J. (International Journal of Sports Science & Coaching, 2024)
Menstrual function is an integral component of the overall health and well-being of cyclically menstruating athletes, impacted by and affecting their participation in sport and athletic training. This review used the coach-athlete relationship to examine the sport environment for factors that facilitate or hinder healthy sport participation for cyclically menstruating athletes with respect to their menstrual cycles. Four databases were searched until June 30, 2023, for studies that explored the experiences, perceptions and knowledge related to the menstrual cycle among athletes training under a coach and coaches of cyclically menstruating athletes. The search produced 2511 studies, which, following screening for relevance and eligibility, resulted in 34 studies of moderate-to-high quality. Thematic synthesis and integration of qualitative and quantitative data from 7558 athletes and coaches from elite to amateur level uncovered 4 main themes pertaining to the coach-athlete relationship and the menstrual cycle that constituted barriers (menstruation taboo, lack of knowledge and awareness, and lack of communication among stakeholders) and facilitators (presence of female coaches, positive experiences of communicating about the menstrual cycle, and trust) to healthy sport participation. A final theme summarised the needs of athletes and coaches related to the menstrual cycle. Greater education, representation of females in sporting roles, and improved collaboration among the various stakeholders emerged as the primary factors for driving a culture-shift in the sporting environment, in order to abolish the taboo against menstruation and promote healthy sport participation for cyclically menstruating athletes.